Alien limb syndrome: A Bayesian account of unwanted actions. (June 2020) - Wolpe, Noham; Hezemans, Frank H.; Rowe, James B.
Abstract: An alien limb is a debilitating disorder of volitional control. The core feature of alien limb is the performance of simple or complex semi-purposeful movements which the patient reports to be unintentional or unwanted, or occasionally in opposition to their intentions. Theories of the mechanism of alien limb phenomena have emphasised the role of disinhibition in the brain, and exaggerated action 'affordances'. However, despite advances in cognitive neuroscience research and a large public and media interest, there has been no unifying computational and anatomical account of the cause of alien limb movements. Here, we extend Bayesian brain principles to propose that alien limb is a disorder of 'predictive processing' in hierarchical sensorimotor brain networks. Specifically, we suggest that alien limb results from predictions about action outcomes that are afforded unduly high precision. The principal mechanism for this abnormally high precision is an impairment in the relay of input from medial regions, predominantly the supplementary motor area (SMA), which modulate the precision of lateral brain regions encoding the predicted action outcomes. We discuss potential implications of this model for future research and treatment of alien limb.